Formakit - López Del Río , Francisca; Dittborn Baeza , Francisco (Base Diseño e Innovación, 2016)
The company emerged as a response to the need of students—especially from vulnerable schools—to have easy access to a material of construction for technological projects. For this purpose we designed a constructive mecano-type system we define as open ended, because it uses common bolts and nuts, enabling students to incorporate into their projects a diversity of pieces created by them.It is a system that empowers individual and group creativity, very easy to use, low cost and that allows to build a very simple project or the skeleton of a robot. The basic pieces of this mecano have been produced in wood and plastic, but currently its been done using only wood for its nobility, beauty and sustainability.In the working process in the classroom, students learn to use basic tools to measure, plot, cut, join and drill thus developing various skills; they also design, use drawings and diagrams to communicate, interpret blueprints, and learn how to work in a team. It also allows them to discover their ability to create a system that works and with which, almost naturally they begin to understand how parts relate to a whole object and what is the role and usefulness of a shaft, gear or a pulley.This material and the models constructed from these systems, have been incorporated, to implement the process of teaching-learning and experimentation, in the subjects of science and technology in elementary education, in technical and professional education and in various programs for teacher training.In addition to its role as a school material, the system is attractive to develop family projects or simply for creative play.